No-drama project management avoiding predictable problems for project success - Gerardi, Bart (Apress, 2011)
No-Drama Project Management: Avoiding Predictable Problems for Project Success is a book for project managers who want or need to be more effective. Having a project crash and burn is never a great situation, author Bart Gerardi explains, but it’s not a career buster—unless the failure appears on the short list of recurring, avoidable problems that can and will pop up during any project. If your project fails due to a lack of planning, for example, expect a trip to the woodshed. Why? Your “unexpected problem” was actually both predictable and avoidable. This book is an exploration of the preventable problems that cause project failures and how to steer clear of them. It includes far more than simple rookie mistakes like trying to please the wrong stakeholder or misunderstanding your role on the team. Those who have been around the block a few times will also find tips and insights that can help them reignite a stalled or meandering career. The sections on managing change adroitly or handling truly unexpected challenges, for example, can get veteran project managers back on track. There are plenty of books about the science of project management that cover such things as creating a work-breakdown structure or a Gantt chart. No-Drama Project Management is about the art of project management. It contains methods and techniques—illustrated with stories from Gerardi’s rich store of experiences—that’ll help project managers shine and become promotable. This book: (1) describes the common obstacles that all projects face, and how to defuse or avoid them, (2) explains how project managers can hold a mirror to their own performance and improve it, and (3) shows project managers how to become masters at expecting the unexpected and thereby ratcheting up their success rates.